Penerapan Algoritma C4.5 Dalam Meningkatkan Kemampuan Bahasa Inggris Pada Mahasiswa - Septri Wanti Siahaan; Kristin Daya Rohani Sianipar; P.P.P.A.N.W Fikrul Ilmi R.H Zer; Dedy Hartama (Sekolah Tinggi Teknik - PLN, 2020)
In this world, many languages ​​from other countries can be used as a communication tool. One of them is English. Students who have education must know that learning English is very much needed. Because nobody knows what will happen in the years to come. It could be one factor to get a job the next few years is our expertise in speaking English. English is a global language used by people to communicate with other people. On this occasion, researchers conducted research to determine what factors can improve students' ability to speak English. To complete this research, researchers resolve by applying the existing algorithm in data mining, namely C4.5 Algorithm. The result of this research can be concluded that the factors that influence to improve students’s ability in English are hearing from the environment. This research has goals is to motivating student in improving their ability of English. Keywords: c4.5 algorithm, English, data mining, ability, improving